An Eco-friendly Strategy for the Synthesis of Spiro-benzimidazoquinazolinone and Spiro-benzothiazoloquinazolinone Derivatives using β-cyclodextrin as a Supramolecular Catalyst - Baranwal, Jyoti; Singh, Swastika; Kushwaha, Smriti; Jyoti, Archana (Current Drug Discovery Technologies, 2024)
Background: Cyclodextrins selectively bind with reactants and facilitate chemical reactions through supramolecular catalysis, similar to the mechanisms employed by enzymes. In this paper, β-cyclodextrin was used as a supramolecular catalyst in water as a green, reusable, and ecofriendly solvent system to synthesize spiro-benzimidazoquinazolinones and spiro-benzothiazoloquinazolinones. Objective: A supramolecular catalyst β-cyclodextrin (β-CD) is used to synthesize spiro- benzimidazoquinazolinones and spiro-benzothiazoloquinazolinones via multicomponent reaction involving the condensation of dimedone, isatin, and 2-aminobenzimidazole/2-aminobenzothiazole. Methods: In a 50 mL round bottom flask were added the respective mixture of substituted isatin (1 mmol), dimedone (1mmol), and 2-aminobenzimidazole/2-aminobenzothiazole (1 mmol) in water (5 ml) containing β-CD (113 mg, 10 mol. %) was stirred at 60oC for 30 min. The desired product was obtained with excellent yield. After completion of the reaction (monitored by TLC), the reaction mixture was quenched with water and extracted with ethyl acetate (4X5 ml). The combined organic layers were washed with brine solution, dried over anhydrous Na2SO4 and evaporated under reduced pressure. The crude product was purified by silica gel chromatography. Results: β-cyclodextrin catalyst showed very good efficiency in the synthesis of the desired compounds and can be easily recovered and reused at least five times with minimal deactivation in catalytic activity. Conclusion: The catalyst demonstrated remarkable effectiveness in producing the target compounds and conducting the reaction with different initial substances, resulting in excellent yields of the products, thereby confirming the broad applicability and versatility of this method.
Keywords: heterocyclic compounds